PENGARUH KEMUDAHAN PENGGUNAAN DAN RISIKO PADA APLIKASI INVESTREE TERHADAP KEPUTUSAN BERTRANSAKSI MENGGUNAKAN FINANCIAL TECHNOLOGY (FINTECH) PEER TO PEER LENDING SYARIAH - Nursyahida, Fadhila Ihsan; Hasanuddin, Muhammad (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2022)
The current financial service operating system has undergone many changes, various financial service operating systems based on digital technology have emerged that can help the activities and needs of the community. This study aims to determine how much influence the ease of use (Ease of Use) and risk on the Investree Application have on the decisions of students who transact in using Financial Technology (Fintech) Peer to Peer Lending Syariah simultaneously. The research uses quantitative research methods, The risk variable from the t test results with an alpha value of 0.05 then HO is accepted and Ha is rejected, because t = 1.696 < t-table = 1.9917 or sig = 0.094 > = 0.05 then there is no effect of risk on the decision to transact using using Peer to Peer Lending Syariah, therefore it can be concluded that the risk variable has a negative and significant effect on the decision to transact using Financial Technology (Fintech) Peer to Peer Lending Syariah. The R² value has a value of 0.642, so it can be stated that the ease of use and risk in the Investree application affect the decision to transact using peer to peer Sharia financial technology (Fintech) together by 41.2%.